2022
DOI: 10.1039/d2qo00976e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed synthesis of cyclopropyl bis(boronates) from aryl olefins and carbon monoxide

Abstract: Cyclopropanes, especially substituted cyclopropanes play important roles in many pharmaceuticals and organic synthesis. In this communication, we introduced a new strategy for the synthesis of diborylated cyclopropanes via a copper-catalyzed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Based on these experimental results and literature precedent, ,, the proposed mechanism of this reaction of styrenes is shown in Figure . Initially, the (L)­Cu–D complex was produced in the presence of NaO t Bu and D 2 .…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Based on these experimental results and literature precedent, ,, the proposed mechanism of this reaction of styrenes is shown in Figure . Initially, the (L)­Cu–D complex was produced in the presence of NaO t Bu and D 2 .…”
mentioning
confidence: 70%
“…Recently, our group developed several copper-catalyzed organic transformations with CO as the carbon or carbonyl source. , In our latest work on Cu-catalyzed carbonylation reactions, we found that carbon carbene species can be formed as key intermediates and were ready for further transformations . Hence, we believe that the carbene species III , which isomerizes from the acyl copper complex via a three-membered-ring state, can also be captured by D 2 .…”
mentioning
confidence: 99%
“…Conveniently substituted cyclopropanes are commonly found in many pharmaceuticals, and may act as intermediates in organic synthesis. [ 148 ] In this regard, Wu [ 149 ] reported an innovative synthesis of diborylated cyclopropanes via a copper‐catalyzed carbonylation process using copper(II) triflate/dppp as catalyst, followed by cyclopropanation (Scheme 83). This reaction was effectively carried out using both internal or terminal aryl olefins, which allowed to prepare in moderate yields (34%—57%), a family of cyclopropyl bis(boronates) (18 examples), with a completely defined stereochemistry.…”
Section: Synthesis Of Fine Chemicals Using Comentioning
confidence: 99%
“…1d). We could obtain a range of different products through the transformations of the in situ generated carbene intermediates including α-C–H insertion, 32 β-C–H insertion, 33,34 CO insertion, 35 and N–H/O–H insertion of carbene. 36…”
mentioning
confidence: 99%
“…1d). We could obtain a range of different products through the transformations of the in situ generated carbene intermediates including a-C-H insertion, 32 b-C-H insertion, 33,34 CO insertion, 35 and N-H/O-H insertion of carbene. 36 With our continued interest in copper-catalyzed borocarbonylation of olens, we speculate that the carbene intermediates can be captured by C]C double bonds to generate cyclopropanes.…”
mentioning
confidence: 99%